LGG-09. LONG-TERM OUTCOMES OF SYMPTOMATIC OPTIC PATHWAY GLIOMA: 32 YEARS OF EXPERIENCE AT A SINGLE TERTIARY CENTER. Issue 2 (22nd June 2018) - Khan, Mumtaz; Lethridge, Robert; Rajagopal, Revathi; Lee, Sharon; Lee, Gabriel; Taylor, Mandy; McGrath, Alycea; Gottardo, Nicholas G
Abstract: OBJECTIVE: To evaluate the long-term outcomes in patients diagnosed with symptomatic optic pathway gliomas (OPGs). METHODS: Retrospective review of all patients with symptomatic OPG treated in a single center from 1984 to 2016. RESULTS: Thirty-seven patients were identified with a median follow-up of 13.74 years (range 1.0-29.6). Eleven (29.7%) of them had NF1. The mean age was 5.8 years and female: male ratio was 1.8:1. Decreased visual acuity was the commonest symptom (75.7%) at presentation. Six cases underwent surgical debulking, 13 were biopsied, and 2 had cosmetic orbital decompression. Histopathological subtypes were pilocytic astrocytoma (n=18) and ganglioglioma (n=1). Seventeen patients received chemotherapy and 18 had radiotherapy. The progression-free survival (PFS) was 53 ± 8.3% at 5 years and 49.7 ± 8.4% at 10, 20 and 25 years. The overall survival (OS) was 97.2 ± 2.7% at 5 and 10 years, 86.1 ± 7.8% at 20 and 77.5 ± 10.8% at 25 years. Twenty-two (59.5%) patients without initial evidence of endocrinopathy developed hormonal defects following therapy. Vision remained unchanged in 15 (40.5%) patients, 14 (37.8%) had visual deterioration at least in one eye, whilst improvement of vision and normal vision were seen in 5 (13.5%) and 3 (8.1%) cases respectively. Second brain tumour was observed in 3 patients at 20.6, 25.3 and 28.7 years post-diagnosis. All 3 had received prior radiotherapy. CONCLUSION: Whilst the PFS remained static after 10 years, the OS dropped after 20 years, due to the occurrence of second malignant brain tumours in patients who received radiotherapy. Significant long-term morbidities were observed in the majority of survivors.